2017
DOI: 10.5271/sjweh.3638
|View full text |Cite
|
Sign up to set email alerts
|

Shift work and cognitive aging: a longitudinal study

Abstract: Shift work, which interferes with circadian rhythms, has evident acute effects on cognitive performance; however, its long-term impact on cognitive development remains unclear. This longitudinal study concluded shift work during midlife impacts neither cognitive performance at retirement nor cognitive trajectories across late life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
4
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 27 publications
3
30
4
1
Order By: Relevance
“…Our finding of no significant association between shift work and dementia is partly in line with previous research. In the Nurses' Health Study, Devore et al (22) found no substantial longitudinal association between night work and cognition and, in a recent study, Bokenberger et al (23) found no longitudinal association between shift work and cognitive aging. In contrast, using cross-sectional data from the VISAT study, Roach et al found indications of lower cognitive efficiency, in terms of immediate free recall, with increasing duration of shift work among males but not among females (20).…”
Section: Comparison With Previous Findingsmentioning
confidence: 97%
See 1 more Smart Citation
“…Our finding of no significant association between shift work and dementia is partly in line with previous research. In the Nurses' Health Study, Devore et al (22) found no substantial longitudinal association between night work and cognition and, in a recent study, Bokenberger et al (23) found no longitudinal association between shift work and cognitive aging. In contrast, using cross-sectional data from the VISAT study, Roach et al found indications of lower cognitive efficiency, in terms of immediate free recall, with increasing duration of shift work among males but not among females (20).…”
Section: Comparison With Previous Findingsmentioning
confidence: 97%
“…Two previous studies based on data from the VIASAT cohort found indications of lower cognitive function among shift workers (20,21), whereas two other studies found no association between shift work and cognitive function (22,23). With dementia as the outcome, one study did not find an association with history of shift work (24), whereas one recent study reported that shift work was associated with mortality due to dementia (25).…”
mentioning
confidence: 96%
“…There is evidence of transient cognitive decline in shift workers [ 9 , 10 ], as well as association with the risk of Alzheimer’s disease [ 11 ] and dementia [ 12 ]. No association with the risk of dementia or accelerated cognitive decline at later life was visible in the recent longitudinal studies [ 13 , 14 ]. However, cardiovascular death as a competing risk is likely to mask potential associations with dementia, because shift workers have increased risk for cardiovascular mortality [ 11 ] and, thus, less likely to become old enough to have dementia, like demonstrated for smoking and dementia [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Por consiguiente, el trabajo a turnos proporciona complicaciones a los ritmos circadianos afectando todo esto al rendimiento cognitivo del individuo (Bokenberger, Ström, Dahl, Åkerstedt, y Pedersen, 2017).…”
Section: Discussionunclassified